2022
DOI: 10.3390/ani12020140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Acting Selenium Preparation on Health and Productivity of Sheep

Abstract: The aim of this study was to determine the effects of long-acting selenium (Se) preparation in sheep. The experimental material comprised Skudda ewes and their lambs. The animals were divided into two equal groups: C-control, and E-experimental. Between days 70 and 80 of pregnancy, group E ewes were injected with Se preparation (Barium Selenate Injection, BVP Animal Care, Ireland) at f 1 mL/50 kg body weight. Hematological, biochemical and immunological blood parameters as well as Se levels were analyzed in ew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…A higher percentage of lymphocytes and monocytes may lead to increased WBC counts in lambs supplemented with inorganic selenium. Similar results were reported by [ 65 ] in ewes, but without a significant increase. A significant increase in leukocyte count compared to the control group was observed when goats were orally administered a high dose of more than 2 mg Se/kg DM [ 63 ].…”
Section: Discussionsupporting
confidence: 92%
“…A higher percentage of lymphocytes and monocytes may lead to increased WBC counts in lambs supplemented with inorganic selenium. Similar results were reported by [ 65 ] in ewes, but without a significant increase. A significant increase in leukocyte count compared to the control group was observed when goats were orally administered a high dose of more than 2 mg Se/kg DM [ 63 ].…”
Section: Discussionsupporting
confidence: 92%
“…Generally, Se is present in a variety of geological locations in the world [20] . Studies indicate that Se functions as an antioxidant [21] immune protect [22] health and reproductive functions [20] in the body. However, animals need a small amount of Se, but larger amounts are harmful [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, Se is involved in regulating the expression of immune genes in bovine support cells, improving sheep humoral and cellular immunity. Moreover, Se can also improve mice immune responses to vaccines [ 29 , 30 , 31 ]. Only a few studies on canine models have demonstrated the regulation of Se on immune functions.…”
Section: Introductionmentioning
confidence: 99%